Estrategias y dinámicas grupales para el proceso de enseñanza aprendizaje de los estudiantes del 10mo año de educación básica de la unidad educativa Carmen Mora de Encalada del cantón Pasaje periodo lectivo 2012-2013 - Zari Ajilla, Christian Stalin (Machala : Universidad Técnica de Machala, 2013)
En la Unidad Educativa Carmen Mora de Encalada del Cantón Pasaje, se realizó la investigación con la temática Estrategias y Dinámicas grupales para el proceso de enseñanza aprendizaje de los estudiantes del 10mo año de Educación Básica de la Unidad Educativa Carmen Mora de encalada del Cantón Pasaje periodo lectivo 2012-2013 cuyo objetivo planteado es Determinar el impacto que produce la aplicación de las Estrategias y Dinámicas Grupales, por parte de los Docentes de Estudios Sociales en la Enseñanza Aprendizaje en los Estudiantes del Décimo Año de Educación Básica de la unidad Educativa Carmen Mora de Encalada del Cantón Pasaje, en el año lectivo 2012 - 2013.
Carmen Mora de Encalada high school, it is located in Pasaje city. In this high school was performed the research with the theme Strategies and Group Dynamics for the teaching-learning process of the students of the 10thyear of Basic Education in the school year 2012-2013.The main goal is determined the impact that the implementation of the Strategy and Group Dynamics, by Social Studies Teacher sin teaching-learning process in the Tenth Year of the students of Basic Education in the Carmen Mora de Encalada high school, of Pasaje in the school year 2012- 2013. The results were achieved through the implementation of interviews and surveys. They were headed both teachers and students of the high school research. The results allowed determining the presence of flaws in the implementation of strategies and group dynamics during the development of classes.
Keywords: ENSEÑANZA; APRENDIZAJE; ESTUDIANTE